Efektivitas Metode Hypnoteaching terhadap Motivasi dan Prestasi Belajar Pendidikan Agama Islam Siswa SMP - Fitri Yanti (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2025)
This study aimed to examine the effectiveness of the hypnoteaching method in improving students’ motivation and academic achievement in Islamic Religious Education (PAI) for grade VII at SMP Negeri 2 Kota Bengkulu. The research employed a quasi-experimental method with a pretest–posttest control group design. The sample consisted of two classes, each divided into an experimental group using the hypnoteaching method and a control group using conventional methods. The results showed significant differences between the two groups, with students taught using hypnoteaching demonstrating higher learning motivation and better academic achievement. In conclusion, the hypnoteaching method is effective in creating a conducive learning environment, enhancing concentration, and fostering both intrinsic and extrinsic motivation. Therefore, this method can be an alternative innovative teaching strategy to improve the quality of PAI learning in secondary schools.   Keywords: Hypnoteaching, Learning Motivation, Academic Achievement, Islamic Religious Education